Comparação histomorfométrica da biomineralização dentinária de compósitos cimentantes in vivo - Caio César Borges de Oliveira (2019)
Biomaterials play an essential role in restoring the dental structure that requires intervention, however, the materials available still have limitations in regard to biomineralization. Composites that combine organic and inorganic materials aim to increase the mechanical properties of the polymeric matrix, uniting properties in order to reduce the disadvantages associated with each of the individual components, as well as to improve the material’s biological response. The present study evaluated the dentin biomineralization induced by experimental composites of Nano- Hydroxyapatite (HAp), Chitosan and Zinc Oxide (ZnO), with and without the addition of Doxycycline, compared to the effect of Calcium Hydroxide (Ca(OH)2) and Glass Ionomer. HAp and ZnO were synthesized and characterized physicochemically. For the in vivo analysis, 66 first molars of 6-weeks-old male Wistar rats were used, which were randomly allocated to 8 different groups, divided into 2 different times according to euthanasia (14 and 30 days) for pulpal stimulation test. After euthanasia, the animals had their maxilla processed histologically. The slides were analyzed using optical microscopy to assess the formation of dentin and the presence of inflammation. Histomorphometric analysis was performed with the aid of Softwares Image J and Adobe Photoshop CC 2018 on the slides of the groups with 30 days, to measure the diameter and depth of exposure, the area of the material, mineralization, tertiary dentin and non-mineralized area, it was also calculated with this data the percentage of mineralization and formation of tertiary dentin. The data were statistically evaluated using the Kruskal-Wallis and Steel-Dwass tests. The results demonstrated a statistically significant reduction in inflammation for the group that received Doxycycline Composite treatment and also the deposit of mineralized matrix in different degrees, progressive closure of the pulp chamber by deposit of organized tertiary dentin in all groups analyzed. The percentage of mineralization in the groups treated with composites with and without the addition of Doxycycline was 64.85% and 57.34%, respectively, compared to 43.36% of Ca(OH)2. It was possible to conclude that the composites were able to induce mineralization areas significantly larger than Ca(OH)2, being not only immediate, but also distant from exposure, with formation of dentinoid tissue suggesting that its use may be beneficial in some pathologies and / or dental trauma.